Rehabilitation in dysfunctions of temporomandibular joints - Maria Dąbrowska; Monika Paruszewska-Achtel; Jakub Lisiecki; Maciej Biernacki; Agata Ulenberg; Grzegorz Ulenberg (Kazimierz Wielki University, 2019)
The treatment of the temporomandibular joints dysfunctions shall be complex due to several possible causes that trigger the disorders. Rehabilitation is based on adopting the techniques that originate from manual therapy, applying physiotherapy, classical and transverse massage, as well as autotherapy. Moreover, in the course of the therapy, Kinesio taping, post-isometric relaxation, positional release, release and rolling of the skin are also applied. Cooperating with an orthodontist, a stomatologist, a physiotherapist and a psychologist, as well as the commitment to the treatment on the part of the patient shall allow the cure to take effect in the joint itself and the muscles surrounding it.